Psychological outcomes of labiaplasty: A controlled prospective study - Sharp, Gemma; Tiggemann, M.; Mattiske, J. (2016)
Background: An increasing number of women are undergoing labiaplasty. However, research on the psychological outcomes for women who undergo this surgery is still limited. Main Objective: To investigate any changes in women’s genital appearance satisfaction, relationship quality, psychological well-being, and quality of life after labiaplasty, relative to a comparison group of women. Methods: Participants were 35 Australian women, aged 18 to 56 years, who underwent a labiaplasty procedure and a comparison group of 30 Australian gynaecological patients, aged 21 to 55 years, who were not seeking labiaplasty. Both groups of women completed a questionnaire (prior to surgery for the labiaplasty group) and a follow-up questionnaire after 6 months. The questionnaires contained standardised measures of genital appearance satisfaction, relationship satisfaction, sexual confidence, psychological distress, self-esteem, and satisfaction with life. Preliminary Results: To date 24 of 30 (80.0 %) women in the labiaplasty group and 17 of 24 in the comparison group (70.8 %) have completed the 6 month follow-up questionnaire. Of the labiaplasty group, 20 (83.3 %) were either “moderately” or “extremely” satisfied with their labial appearance at 6 months post - surgery.In addition, 21 (87.5 %) were “moderately”/”extremely” satisfied with the physical function of their labia. Complications were reported by 8 women (33.3 %), including pain and infections. Of all the standardised psychological outcome measures employed, there was only one significant group x time interaction effect whereby the labiaplasty group’s genital appearance satisfaction significantly increased from pre- to post-surgery with a large effect size, relative to the comparison group. Conclusions or Comments: The study results thus far suggest that most women who have a labiaplasty are satisfied with the irsurgical results. Furthermore, having a labiaplasty appeared to significantly improve women’s satisfaction with their genital appearance. However, to date, no significant effects have been found for relationship quality, psychological well-being, or quality of life.